Salud mental en las comunidades rurales del Ecuador. - Narváez Arias, Daniela Monserrath (2025)
This study aims to analyze the state of mental health in rural communities of Ecuador. It is a bibliographic and descriptive-level investigation, based on the review of 17 scientific articles selected through a systematic search in databases such as Scielo, Dialnet, and Google Scholar, using Boolean operators and keywords related to mental health in rural communities. The methodology followed the PRISMA approach for screening and evaluating the articles, excluding duplicates, irrelevant works, or those with restricted access. The results indicate that mental health in Ecuador's rural communities is in a highly vulnerable state, with the main identified disorders being depression and anxiety, often associated with socioeconomic factors such as unemployment, economic hardship, and family instability. Significant comorbidities are also highlighted, including suicide and the relationship between depressive disorders and problematic substance use. The main barriers to accessing mental health services include financial difficulties, geographic distance to specialized centers, and cultural prejudices. However, there is an increasingly favorable perception toward seeking professional help. In conclusion, the study highlights the need for public policies focused on improving the coverage and accessibility of mental health services in Ecuador’s rural communities.